The Connotative Meanings of Emotion Words in Conan Gray's Superache Album - Levia, Alzena; Rahayuni, Ni Ketut Sri; Adni, Nissa Puspitaning (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This research aims to analyze the connotative meanings of emotion words in Conan Gray’s Superache Album. This study focuses on identifying the types of connotative meanings associated with emotion words in the lyrics and examining how these contribute to the emotional messages conveyed in the songs. A qualitative approach, incorporating text analysis, is employed to analyse and interpret emotion words and their connotative meanings. The theories used in this study are the theory of Connotative Meaning by Leech (1981) and the Theory of Emotion Words by Kövecses (2000). The research revealed that Conan Gray’s Superache album encompasses a diverse range of emotions, with connotative meanings in its song lyrics, primarily centered around themes such as love, heartbreak, and emotional vulnerability, which are predominantly associated with the emotion of sadness. The results of the findings indicate that 10 emotion words with connotative meanings were identified in the album's lyrics, with sadness being the most dominant emotion, appearing at a frequency of 6. Negative connotations occur most frequently, followed by positive connotations. This study highlights how Conan Gray effectively communicates deep emotional and social messages through emotionally charged lyrics.